Edge Computing Based Electricity-Theft Detection of Low-Voltage Users - Zheng, Yingjun; Chen, Feng; Yang, Hongming; Su, Sheng (Frontiers in Energy Research, 2022)
Electricity theft of low voltage (LV) users could result in not only escalation of power loss but also dangerous electric shock. Since LV users are served by distribution transformers, electricity theft of an LV user will cause line loss escalation of the associated distribution serving zone (DTSZ). Therefore, it seems promising to identify anomaly users of electricity theft with a granger causality test to find out the user causing an escalation of line loss in DTSZ with time series of users’ usage and line loss. However, meters of LV users in severe environments suffer from communication failure to upload metering data to the head end of Advanced Metering Infrastructure (AMI) occasionally, which could distort the daily electricity usage of the associate user. Consequently, it could cause false alarms unavoidably once we detect electricity theft with these distorted data. Since the distribution transformer unit (DTU) collects metering data of LV users within associate DTSZ without distortion, an edge computing based electricity theft detection approach is proposed in this paper. The correlation between line loss of a DTSZ and electricity usage of anomaly users of electricity theft is first analyzed. Thereafter, the granger causality test is employed to identify anomaly users with authentic usage data with edge computing in DTU. Finally, the abnormal data and the data repaired by different missing data filling algorithms are used on the main station to detect electricity theft. Numerical simulation suggests that although missing data completion could recover information in missing data partially, it could result in notable false positive alarm in electricity theft, while the proposed method based on edge computing can completely eliminate the data distortion caused by communication failure.